Detection, virulence and antimicrobial resistance of Yersinia enterocolitica in bulk tank milk in Italy. (September 2018) - Bonardi, S.; Le Guern, A.S.; Savin, C.; Pupillo, G.; Bolzoni, L.; Cavalca, M.; Pongolini, S.
Abstract: In 2016 and 2017, 509 raw milk samples were collected from bulk milk tanks in 315 dairy farms in Parma province, Italy. Yersinia pseudotuberculosis was never detected. Yersinia enterocolitica was isolated from 17 (3.1%) bulk milk samples by culture methods. Estimated apparent prevalence was 3.91% in 2016, and 2.63% in 2017, with no significant difference between the two years (df = 1; p -value = 0.419). Five BT 2/O:5, 27 and 12 BT 1A isolates were detected. The most common virulence genes ( ail, inv, virF, yadA, ystA, ystB, myfA, irp2, fyuA ) were screened and the genes ail, virF, yadA, ystA were harboured only by 2 O:5, 27 isolates. The Italian strains were very close by SNP analysis. The 2 O:5, 27 isolates showed a unique antimicrobial resistance pattern, being resistant to amoxicillin, cefoxitin, cephalexin and amoxicillin - clavulanic acid. The study suggests that consumption of raw or improperly pasteurised milk may be hazardous for the consumers.